Evaluation of Project Based Learning Model Trough online Settings to Increase Science Learning Outcomes - Novitasari, Erma; Mediatati, Nani (Universitas Negeri Semarang, 2021)
During the corona virus pandemic (covid-19) learning existing in the 2013 curriculum must be implemented. The study is to evaluate the increase of students' learning through the PJBL project based learning model with the online setting on science subjects for 5 grade of elementary school. This study is classroom action research with two cycles. The population in the study amounted to 21 and the sample used using the saturated sample. The Instruments in this study were observations and tests of students' learning results. The data collected techniques in this study application were for observation taken by the supervisor, namely the elementary school teacher and also student science test results. The data analysis technique in this study was descriptive and N-gain analysis. The results showed increases in the average result of study and achievement. In the N-gain test, the increase was in moderate categories. It is absorbed by the use of a PJBL with an online setting on a science class lifts everyday life materials so it is easier for the student to run a work project that enhances his studies. Therefore, the PJBL in this research was well implemented.